Da'wah Strategy of West Java Nahdlatul Ulama (NU) with Health Message Content in Facing the Covid-19 Pandemic - Ma'arif, Bambang Saiful; Siddiq, Asep Ahmad (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This research aims to discuss the da'wah strategy of the Islamic organization Nahdlatul Ulama (NU) of West Java in dealing with the COVID-19 pandemic. A lot of information about health is received by the congregation; some are true and some are not. Unfortunately, many residents and congregations are influenced by things that are not true, making them reluctant to be vaccinated. This research method is qualitative with in-depth interview techniques. This study concludes that the PWNU (Nahdlatul Ulama Regional Boards) da'wah strategy begins with the organization's view of COVID-19 which gave birth to NU's da'wah policy and its da'wah strategy. COVID-19 is a test that needs to be addressed and overcome properly. NU policy leads to actions to overcome the pandemic, which are synergized with the government and society by utilizing organizational resources to foster jam'iyyah and congregational health. Da'wah is carried out by conveying religious messages combined with spiritual and mental health information to achieve physical health, accompanied by worship and good endeavor. In addition, reading the Qur'an can also bring happiness that affects physical endurance and health. Communication media are used to deliver da’wah messages from West Java NU, namely through mass media and social media, in which social media is more intensely used for da'wah than mass media. The implication of this research is that da'wah by Islamic organizations can still be carried out during a pandemic by using communication media, both social and mass media.